Dentro de Tailandia salvaje - Ryan, Marla Felkins; Corwin, Jeff.; Discovery Channel (Firm) (Detroit : Blackbirch Press, 2005)
Television personality Jeff Corwin takes the reader on an expedition through Thailand, and introduces some of the diverse wildlife found there.
Keywords: Corwin, Jeff; Spanish language materials; Animals -- Thailand -- Juvenile literature; Wildlife conservation -- Thailand -- Juvenile literature; Thailand -- Description and travel